Pacing strategy and resulting performance of elite trail runners: insights from the 2023 World Mountain and Trail Running Championships - Jaén-Carrillo, D.; Margarit-Boscà, A.; García-Pinillos, F.; Holler, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Pacing is crucial in endurance sports such as running, and its importance is also prominent in trail running due to the unique challenges, including high elevation gains and varied terrain. This study aimed to explore the pacing strategies of elite athletes during the 2023 World Mountain and Trail Running Championships for the Trail Short distance.